Availability of marine collagen from Newfoundland fisheries and aquaculture waste resources. (September 2019) - Dave, Deepika; Liu, Yi; Clark, Lesley; Dave, Nisarg; Trenholm, Sheila; Westcott, Jillian
Abstract: Atlantic salmon and Atlantic cod are two main finfish species harvested from Newfoundland aquaculture and wild capture fisheries, respectively. During processing, a large amount of by-products containing many valuable components are disposed of or used for low value. Lumpfish, a cleaner fish, is also not utilized at the end of the season. The proximate composition and available collagen content were investigated for Atlantic salmon and wild cod by-products and lumpfish. The highest moisture content was found in whole lumpfish (91.08%). The ash level (dry basis) was highest in fins of cod (38.14%), followed by salmon (32.19%) and lumpfish (19.06%). Salmon frames showed higher lipid content (44.81% on dry basis). The protein content (dry basis) was highest in skin of cod (96.72%), followed by salmon (71.51%) and lumpfish (77.32%). The highest collagen content was found in salmon scales and skin (51.11% and 27.45% of dry matter, respectively). Highlights: Fins of all fishes studied were rich in ash for potential marine mineral extraction. Salmon frames and skin were abundant in lipid for potential fish oil extraction. Salmon and cod skin were high in protein for protein and amino acid production. Salmon scales and skin have high collagen amount for high-value collagen production.